Immuno-PCR in cancer and non-cancer related diseases: a review. Issue 2 (2nd April 2016) - Assumpção, Anna Luiza F. V.; da Silva, Rodrigo C.
ABSTRACT: Polymerase chain reaction-amplified immunoassay (immuno-PCR, iPCR) is a method that combines the specificity of an immunological detection method and the sensitivity of a nucleic acid amplification method. In this way, immuno-PCR uses a minimum amount of sample, and allows the detection of rare diseases and those diseases in very early stage (i.e. infectious diseases, degenerative disorders, or neoplastic diseases). The present review was aimed to describe this new methodology and applications to the early detection of cancer and non-cancer related diseases, and discuss about the possibility to detect diverse biomarkers of oncology disorders, such as breast, gastric, colorectal and nasopharynx cancer, and other factors related to the growth of the neoplastic disease.